Implementasi Forward Chaining Untuk Mendeteksi Attention Deficit Hyperactivity Disorder (ADHD) Pada Anak Berbasis Web Responsif - Imroatul Bilad; Budiman Budiman; Muhammad Gugus Azhari (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) if defined in general describes the condition of children who show signs or symptoms of lack of concentration (inattentive), can't stay still (hyperactivity), and act as they please (impulsivity). Lack of teacher supervision and attention at school can cause a child to experience ADHD symptoms. Among them are children who play as they please, cannot sit still and listen, like to annoy their friends and make it difficult to concentrate. Diagnosis of hyperactivity or ADHD is usually done by an expert or psychologist. But actually teachers or parents can make early detection of the possibility of ADHD in children by observing children's behavior at school or at home from the way they communicate, interact socially with their peers, and the child's imagination ability. The expert system is a solution to assist teachers and parents in early detection of possible ADHD. The expert system is designed based on responsive web by utilizing the forward chaining method as an inference engine. The research method used is data collection methods ranging from observations to literature studies that are built and structured using use case diagrams and PHP as a programming language and MySQL as a database storage. With the system that has been built, it is hoped that it will provide benefits for users in early detection of the symptoms and types of ADHD disorders.